Longitudinal analysis of Brain Metabolite levels for HIV infected Children from ages five to eleven - Van Biljon, Noëlle (Department of Statistical Sciences, 2020)
HIV infected (HIV+) children initiate antiretroviral therapy (ART) early in life and remain on it lifelong. However, the long-term impact of ART and HIV on the maturing brain is not well documented and longitudinal neuroimaging studies are rare, especially in developing countries most heavily impacted by HIV/AIDS where access to imaging resources are limited. We have examined HIV related changes in metabolite level trajectories from 5-11 years in three brain regions using Magnetic Resonance Spectroscopy (MRS). We used univariate linear mixed effect models to identify independent profiles of the metabolites measured in each region of the brain. To explore the metabolite trends in a multivariate setting we generated multilevel mixed effects models, and correlated response models. There was an element of confounding introduced through the change of MRI scanner during the follow-up period and we compare different methods to resolve this issue. Consequently, we did observe differences in metabolite profiles from HIV+ children compared to HIV uninfected (HIV-) controls. This suggests that while these children are on ART treatment, there is still some underlying effect on their neurochemistry which sets their development apart from the normal healthy profiles we expect.